Unsupervised Pattern Recognition for Geographical Clustering of Seismic Events Post M W 7.8 Ecuador Earthquake - Inostroza-Ponta, M; Alcivar-Cevallos, R (IEEE Computer Society, 2018)
Ecuador is located at the collision point of Nazca and South America tectonic plates, an area with high seismic activity; hence it is common that a large number of seismic events occur annually. On April 16, 2016, a Mw 7.8 earthquake impacted coastal Ecuador, and plenty of aftershocks were located within the affected and surrounding areas. Determining similar seismic geographical zones of the such events has become a problem of great interest for post-earthquake mitigation actions. In this paper, we present an approach to cluster seismic events post Mw 7.8 Ecuador earthquake. We carried out unsupervised pattern recognition through a clustering algorithm called MST-kNN. Our approach identified five clusters with similar seismic geographical zones along coastal provinces and Pacific Ocean. The results can be used to plan post-earthquake mitigation strategies such as identifying safe roads for evacuation plans or adequate location of ad hoc health and supply centers. © 2018 IEEE.